Effect of yeast and cell wall of Saccharomyces cerevisiae supplement on body weight gain, feed conversion and carcass traits in Rambouillet lambs - Mariezcurrena-Berasain, María Antonia (2019)
The aim of this study was to evaluate the effect of the complete yeast supplement (LC) and the cell wall (PcSc) of Saccharomyces cerevisiae on the weight gain, feed conversion and characteristics of the carcass in Rambouillet lamb. The treatments were: T1 (without LC and without PcSc), T2 (1 g/kg-1 MS LC) and T3 (0.6 g/kg-1 MS PcSc) with six repetitions (lambs) per treatment. The experiment lasted 55 days. Eighteen lambs (36.5 ± 2.5 kg) were housed in individual pens and received water and a diet that provided 14.8% protein and 12 384.64 kJ/kg-1 MS. Daily weight gain and feed conversion were evaluated during fattening, as well as the weight of the hot and cold carcass, pH, temperature (45 min and 24 h) and target color (24 h) of the carcass. There were no significant differences for daily body-weight gain or for feed conversion due to the treatments, but in the color characteristics the variables a* and C had a significant difference (p<0.05) when adding LC or PcSc.